Handbook of Research on Oncological and Endoscopical Dilemmas in Modern Gynecological Clinical Practice - Dinas, Konstantinos (IGI Global, 2020)
For the past decade or so, research regarding women's health has become a major source of concern among health professionals. Due to the vast amounts of research, it has been difficult to amass a comprehensive source describing the challenges of physicians in this area of medical treatment and care. The Handbook of Research on Oncological and Endoscopical Dilemmas in Modern Gynecological Clinical Practice is a pivotal reference source that provides vital research on the application of clinical practices in regards to the health of women and prevention of severe, life-threatening diseases. Whil.